Lack of an Association between Autoimmune Pancreatitis and Varicella Zoster Virus - Patel, Neal C; Palmer, William C; Krishna, Murli; Lewis, Michele D; Wallace, Michael B (JOP. Journal of the Pancreas, 2011)
No abstract available.